Self-development and social transformations?: the vision and practice of the self-study mobilization of Swadhyaya - Giri, Ananta Kumar (Rawat Publications, 2008)
Articles with reference to community development and social change in Gujarat, India, initiated by the Swadhyaya movement, inspired by Pandurang Vaijnath Athavale, b. 1920